Nitric oxide and oxidative stress pathways do not contribute to sex differences in renal injury and function in Dahl SS/Jr rats - Turbeville, Hannah R. (Physiol Rep, 2020)
The burden of hypertension in the United States is increasing and yields significant morbidity and mortality, and sex differences in hypertension are widely recognized. Reduced nitric oxide (NO) bioavailability and increased oxidative stress are known to contribute to the pathogenesis of hypertensive renal injury, and but their contributions to sex differences in injury progression of are undefined. Our purpose was to test the hypothesis that male hypertensive rats have accelerated renal injury compared to females and to determine the contributions of the nitric oxide pathway and oxidative stress in these differences. Male and female Dahl SS/Jr rats, a model that spontaneously develops hypertension with age, were allowed to age on a 0.3% NaCl diet until 3 or 6 months of age, at which points blood pressure was measured and plasma, tissue, and urine were collected. While no significant sex differences in blood pressure were present at either time point, renal injury measured by urine protein excretion was more severe (male = 44.9 ± 6; female = 15±3 mg/day/100 g bw, p = .0001), and renal function was reduced (male = 0.48 ± 0.02; female = 0.7 ± 0.03 ml min(‐1) g(‐1) kw, p = .001) in males compared to females with age. Both male and female rats exhibited reduced nitric oxide metabolites (3 months: male = 0.65 ± 0.1; female = 0.74 ± 0.3; 6 months: male = 0.16 ± 0.1; female = 0.41 ± 0.1 ml min(‐1) g(‐1) kw, p, age = 0.02, p, sex = 0.3). Levels of urinary TBARS were similar (3 months: male = 20±1.5; female = 23±1.8; 6 months: male = 26±4.8; female = 23±4.7µM day g(‐1) kw, p, age = 0.4, p, sex = 0.9), extracellular superoxide dismutase (EC SOD) mRNA was greater in females (3 months: male = 0.35 ± 0.03; female = 1.4 ± 0.2; 6 months: male = 0.4 ± 0.05; female = 1.3 ± 0.1 normalized counts, p, age = 0.7, p, sex < 0.0001), but EC SOD protein expression was not different (3 months: male = 0.01 ± 0.002; female = 0.01 ± 0.002; 6 months: male = 0.02 ± 0.004; female = 0.01 ± 0.002 relative density, p, age = 0.2, p, sex = 0.8). These data support the presence of significant sex differences in renal injury and function in the Dahl S rat and identify a need for further study into the mechanisms involved.